3D digital subtracted CT angiography to evaluate the venous anatomy in extra-axial tumors invading the major dural venous sinuses. Issue 4 (August 2017) - Lenck, Stéphanie; Bresson, Damien; Bernat, Anne-Laure; Saint-Maurice, Jean-Pierre; Labeyrie, Marc-Antoine; Froelich, Sébastien; Houdart, Emmanuel
Background: Investigation of the venous system surrounding a tumor that is invading a dural sinus is of great use for guiding the surgical excision. Non-invasive imaging is often inadequate since enhancement of the tumor causes it to blend with the contrast of the venous vascular structures. Conventional two-dimensional angiography is also often insufficient. Objective: The objective of this study was to report regarding the potential of three-dimensional digital subtracted computed tomography angiography (3D DS-CTA) as a technique to preoperatively explore these tumors. Methods: We retrospectively studied the radiological and surgical features of patients explored with 3D DS-CTA for a tumor invading a major dural sinus. Results: Three patients were included in this study, one hemangiopericytoma and two meningiomas. 3D DS-CTA allows for accurate assessment of the patency of the sinus, the location of the secondary intra- and trans-osseous venous outlets, and surgical guidance by neuronavigation. Conclusion: 3D DS-CTA could be a promising guiding and diagnostic tool for the pre- and intraoperative treatment of vascular tumors invading the dural sinuses, for which the venous morbidity and mortality is substantial.